Prevalence of Chlamydia trachomatis and Neisseria gonorrhoeae co-infections among patients with newly diagnosed syphilis: a single-centre, cross-sectional study - Rob, Filip; Jůzlová, Kateřina; Kružicová, Zuzana; Vaňousová, Daniela; Lásiková, Šárka; Sýkorová, Blanka; Machala, Ladislav; Rozsypal, Hanuš; Veselý, Dan; Zákoucká, Hana; Hercogová, Jana (Central European journal of public health, 2019)
OBJECTIVES: The aim of the study was to determine the prevalence of Chlamydia trachomatis and Neisseria gonorrhoeae co-infections among patients with newly diagnosed syphilis. METHODS: In patients with any stage of newly diagnosed syphilis swabs were performed from urethra, rectum, pharynx and cervix according to the gender and type of sexual intercourse. From these smears standard validated nucleic acid amplification tests (NAATs) for Chlamydia trachomatis and Neisseria gonorrhoeae infections were done. RESULTS: From 548 (488 men, 60 women) screened patients co-infection was detected in 15.9% of the cases. The majority of the co-infections (86.2%) were asymptomatic. The overall prevalence of chlamydial infection was 11.1% and 8.8% for gonococcal infections. In men who have sex with men (MSM) the prevalence of co-infections was significantly higher (20.0%) than in heterosexual men and women (4.2%) (p < 0.001). In MSM patients the presence of co-infection was significantly associated with HIV infection (p < 0.001). Among MSM 9.6% of the tests detected infection in anorectal site, while prevalence in urethral (2.8%) and pharyngeal (2.4%) localization was significantly lower. In heterosexual patients prevalence was less than 2.0% in all anatomic sites. CONCLUSIONS: The implementation of screening tests in case of sexually transmitted infections in patients with newly diagnosed syphilis is an important part in the management of this disease. These results suggest that screening of asymptomatic heterosexual patients leads to detection of minimum co-infections, but in MSM (especially HIV positive) should always be performed at least in anorectal site, where asymptomatic co-infections are common.
Keywords: screening; Female; Prevalence; Homosexuality, Male; ženské pohlaví; průřezové studie; syphilis; HIV Infections; Coinfection; chlamydia; lidé; syfilis; homosexualita mužská; Chlamydia Infections; koinfekce; HIV infekce; chlamydiové infekce; prevalence; gonorea; Cross-Sectional Studies; Male; Gonorrhea; Chlamydia trachomatis; MSM; gonorrhea; Syphilis; Neisseria gonorrhoeae; mužské pohlaví; Humans